Capital markets development and economic growth in eSwatini - Orwothwun, Noel (Graduate School of Business (GSB), 2026)
Capital markets within Eswatini have continued to grow, predominantly in size, as evidenced by leaps in the capitalisation of both equity and debt available to trade over recent years. That said, they remain relatively underdeveloped, driven by inefficiencies stemming from low levels of liquidity, low volumes of listings, and a thin investor base. Considering existing efforts to develop the capital markets, this study sought to examine the impact that capital markets development has on economic growth in Eswatini. To do so, the study applied ARDL and error correction model techniques to estimate the long-run and short-run effects of capital markets development on economic growth in Eswatini between 2013 and 2023. The model estimates indicated the existence of significantly positive long-run effects of capital market liquidity, proxied by equity turnover, and capital market size, proxied by corporate and government bonds outstanding, on economic growth in Eswatini. Conversely, the model estimates also indicated that capital market size proxied by equity market capitalisation had an insignificant effect on Eswatini's economic growth. Furthermore, the study found that Eswatini's net exportation of goods and inflation, which served as control variables, had significantly positive and negative long-run effects, respectively, on economic growth. That said, the study recommends that the Government of Eswatini's policy directions include mechanisms that focus on improving capital market efficiency through broadening the investor base and instruments available for investors to participate at low cost.